Enhancing Language Development through Multisensory Media Interventions: A Classroom Action Research Study with Children Experiencing Speech Delays - Agustina, Ramlah; Azizah, Nur (Papanda Publisher, 2025)
Speech delays affect approximately 5-10% of preschool children and can significantly impact cognitive, social, and academic development. Multisensory interventions that engage visual, auditory, tactile, and kinesthetic modalities show promise for enhancing language development, yet limited research exists regarding their effectiveness for children with speech delays. This study aimed to evaluate the effectiveness of multisensory media interventions in improving expressive and receptive language abilities among children with speech delays. A classroom action research design following the Kemmis and McTaggart model was implemented across two cycles at TK Negeri Pembina 2 Muara Bengkal, East Kalimantan. Two children with identified speech delays (MH and MS) participated in systematic multisensory interventions incorporating audio flashcards, manipulative objects, and movement-based activities. Language abilities were assessed using structured protocols measuring expressive and receptive language performance, with a predetermined success criterion of 75% achievement. Both subjects demonstrated substantial improvements from baseline to post-intervention. Subject MH progressed from 25% to 75% in expressive language and 33% to 75% in receptive language. Subject MS advanced from 33% to 75% in expressive language and 42% to 83% in receptive language. Both participants achieved age-appropriate developmental status by Cycle II. Multisensory media interventions effectively enhanced language development in children with speech delays, supporting theoretical frameworks emphasizing multi-modal learning approaches for children with developmental challenges.